A hero's challenged masculinity: Darín in La señal (2007). Issue 2 (3rd May 2016) - Rocha, Carolina
Abstract: This article analyzes the paradoxical role of Argentine film star Ricardo Darín as El Pibe Corvalán in the noir film La señal (2007). Darín's prominence is challenged by both the presence of a buddy detective, Corvalán, played by actor Diego Peretti, and a femme fatale, Gloria (Julieta Díaz). Drawing on psychoanalytical theory, I investigate Corvalán's inscription into and/or distance from the Law-of-the-Father as a way to examine his performance of masculinity in La señal . I also focus on the woman who attracts the hero's desire, suggesting that La señal presents the vulnerability (rather than the victory) of the non-Peronist, middle-class protagonist – and that of patriarchy in general as well.